ARAB SOCIALISM IDEA OF JAMAL ‘ABD AL- NASIR - Wisyly Wahab (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2017)
Many observers valued that Nasir’s socialism can’t be separated with communism and non- Islam economic theory, but Nasir together with his supporters has a principle consistently and commit to prove Arab Socialism that proclaimed has Islamic root. May be this special character that distinguishes it from the others.By the width of the area as covering of Nasir’s Arab Socialism and takes part in the need of the same Moslem ethnic, formulates social change in Egypt, and also formulates again social- culture which is being going to rise in Arab world, so the focus of this socialism directs to “ Islamism “ form.